The Natural Carotenoid Crocetin and the Synthetic Tellurium Compound AS101 Protect the Ovary against Cyclophosphamide by Modulating SIRT1 and Mitochondrial Markers. (15th November 2017) - Di Emidio, Giovanna; Rossi, Giulia; Bonomo, Isabelle; Alonso, Gonzalo Luis; Sferra, Roberta; Vetuschi, Antonella; Artini, Paolo Giovanni; Provenzani, Alessandro; Falone, Stefano; Carta, Gaspare; D'Alessandro, Anna Maria; Amicarelli, Fernanda; et al.
Abstract : Cancer therapies are associated with increased infertility risk due to accelerated reproductive aging. Oxidative stress (OS) is a potential mechanism behind ovarian toxicity by cyclophosphamide (CPM), the most ovotoxic anticancer drug. An important sensor of OS is SIRT1, a NAD + -dependent deacetylase which regulates cellular defence and cell fate. This study investigated whether the natural carotenoid crocetin and the synthetic compound AS101 protect the ovary against CPM by modulating SIRT1 and mitochondrial markers. We found that the number of primordial follicles of female CD1 mice receiving crocetin plus CPM increased when compared with CPM alone and similar to AS101, whose protective effects are known. SIRT1 increased in CPM mouse ovaries revealing the occurrence of OS. Similarly, mitochondrial SIRT3 rose, whilst SOD2 and the mitochondrial biogenesis activator PGC1- α decreased, suggesting the occurrence of mitochondrial damage. Crocetin and AS101 administration prevented SIRT1 burst suggesting that preservation of redox balance can help the ovary to counteract ovarian damage by CPM. Decreased SIRT3 and increased SOD2 and PGC1- α in mice receiving crocetin or AS101 prior to CPM provide evidence for mitochondrial protection. Present results improve the knowledge of ovarian damage by CPM and may help to develop interventions for preserving fertility in cancer patients.